Cytotaxonomy of the genus Dichromatos Cigliano 2007 (Orthoptera, Acridoidea, Melanoplinae). - Ferreira, Amilton; Mesa, Alejo (Pensoft Publishers, 2010)
All four species of the genus Dichromatos now cytologically analyzed, including D. montanus and D. comp (Cigliano 2007), studied in the present paper, are 2n = 21([male])/22([female]) (FN = 23/24) with a X1X2Y [male] / X1X1X2X2 [female] sex-determination mechanism. The possibility that this mechanism arose from a single ancestral species from which a rapid process of speciation and dispersion took place is discussed.